2007
DOI: 10.1108/00483480710716740
|View full text |Cite
|
Sign up to set email alerts
|

Reforming further education: the changing labour process for college lecturers

Abstract: Purpose -The purpose of this article is to examine how the labour process of further education lecturers has changed as a result of legislative reforms introduced in the early 1990s. Design/methodology/approach -The paper draws on labour process theory and emergent perspectives on "the new public management" to provide theoretical frameworks. Evidence is derived from research carried out at three FE colleges in the English West Midlands involving interviews with managers and lecturing staff, documentary materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 52 publications
(45 reference statements)
2
28
0
2
Order By: Relevance
“…The education sector is often seen as a site of managerialism ( Gleeson and Knights, 2008;Mather and Worrall, 2007) that has eroded teacher autonomy and deprofessionalised the workforce (Avis and Bathmaker, 2004;Mather, Worrall and Seifert, 2009) via the implementation of strategies of surveillance and punitive performance management. The result is work intensification (Mather, Worrall and Seifert, 2008) which leads to the boundaries between work and home life becoming ever more permeable as was evidenced in this study with the majority of respondents doing work at home, 40.07% extensively or very extensively -with increasing levels of work to do, teachers are subject to 'home invasion' (Page, 2011b), completing tasks at home in an effort to meet their responsibilities.…”
Section: Discussionmentioning
confidence: 99%
“…The education sector is often seen as a site of managerialism ( Gleeson and Knights, 2008;Mather and Worrall, 2007) that has eroded teacher autonomy and deprofessionalised the workforce (Avis and Bathmaker, 2004;Mather, Worrall and Seifert, 2009) via the implementation of strategies of surveillance and punitive performance management. The result is work intensification (Mather, Worrall and Seifert, 2008) which leads to the boundaries between work and home life becoming ever more permeable as was evidenced in this study with the majority of respondents doing work at home, 40.07% extensively or very extensively -with increasing levels of work to do, teachers are subject to 'home invasion' (Page, 2011b), completing tasks at home in an effort to meet their responsibilities.…”
Section: Discussionmentioning
confidence: 99%
“…The same study revealed that professional groups within the NHS attempted to resist what they perceived to be the degradation of their own labour process as aspects of their work were reallocated to less qualified, less unionised-and cheaper-workers. Labour cheapening strategies have also been found in other parts of the public sector, Mather et al (2007) reveal how contracts were rewritten and imposed upon FE lecturers by senior management with those failing to accept new contracts being disallowed pay increases or being forced to accept the new contract if they wanted promotion. They argued that the imposition of the so-called 'professional contract' was something of a semantic twist, in that most lecturers saw the contract as having been designed to deprofessionalise them by reducing their autonomy while simultaneously intensifying and extensifying their work.…”
Section: Discussionmentioning
confidence: 97%
“…Ironside and Seifert (2004) argue that this shift was underpinned by a deeper ideological belief in the perceived superiority of markets (and capitalism) over the hitherto received wisdom of state provision of essential public services (Dunsire 1999). Mather et al (2007) argued that both the antecedents and consequences of such political shifts may be understood by reference to Braverman's (1974) analysis of the relationship between capital and labour with labour process theory offering a conceptually coherent framework that accounts for the impetus underpinning organisational change in the public sector and for its consequences on those working in the sector. Both Corby and White (1999) and Pendleton and Winterton (1993) draw on evidence from across the public sector to testify as to the impact this has had on public sector employee relations.…”
Section: Market Ideology and "Modernisation"mentioning
confidence: 99%
“…Consequently, the increasing proportion of women in FE could be seen as a result of the on-going degradation of this work as it becomes less well-rewarded, deskilled and codified. Following Braverman, the increasing employment of women could be interpreted as an influx of a 'reserve army of labour' as an effect of the removal of colleges from the protection of LEA control that traditionally shielded FE teachers from an excessive exploitation of their labour (Mather et al 2007;Simmons 2006). Such views came through in some of the interviews, for example:…”
Section: Explaining the Feminisation Of Fementioning
confidence: 99%